Risk factors associated with eating behavior in climacteric women assisted in Primary Health Care (Research, Society and Development, 2022)
The purpose of this study was to analyze the risk factors associated with eating behavior in climacteric women assisted in Primary Health Care. Methods: This is a cross-sectional study with a random sample composed of 874 women aged between 40 and 65 years assisted in Family Health Strategies units in Montes Claros, Minas Gerais, Brazil. The following variables were investigated: sociodemographic, menopausal and behavioral characteristics. The outcome was food consumption, a score was created and dichotomized into healthy and unhealthy, with the cut-off point being the mean value. Descriptive analyzes of all variables were performed, as well as bivariate analyzes using the chi-square test. After being selected for multiple analysis, the Poisson regression model with robust variance was used, in a hierarchical manner consisting of blocks of variables at distal, intermediate and proximal levels. At the distal level, income below one minimum wage (PR=1.33) was associated with unhealthy eating behavior. At the intermediate level, the variables that remained associated with the outcome after adjustment were perimenopausal climacteric (PR=0.75) and no menstruation in the last 12 months (PR=0.68). At the proximal level, alcoholism (PR=1.35) and sedentary lifestyle (PR=1.52) remained significantly associated with food consumption. Climacteric women showed a relevant prevalence of unhealthy eating behavior associated with sociodemographic, climacteric and lifestyle characteristics.